Thysanoteuthis rhombus Troschel, 1857 (Teuthida: Thysanoteuthidae) Diamond squid, registered from coastal area of Ica, Peru - Roque-Sánchez, Máximo A. (2021)
In this paper, Thysanoteuthis rhombus is first registered in the coast of Pisco and its distribution range in the Eastern Pacific is extended to Ica, Peru. A 68 cm LM specimen was captured between 13°50'00"S and 77°08'00"W at 50 meters depth. A brief description of the species is given, with taxonomic observations and comments on its geographic distribution and fishery.